A revision of Boreantrops Kits & Marshall (Diptera: Sphaeroceridae: Archiborborinae) - Kits, Joel H.; Marshall, Stephen A. (Zootaxa, 2015)
Boreantrops Kits & Marshall is a recently described genus of flies in the family Sphaeroceridae. Species occur from Brazil and Bolivia north to northern Mexico, mostly in humid montane environments. Two species were included in the genus when originally described, B. calceatus (Duda) and B. mexicanus (Steyskal). Here we revise the genus to include 32 species, including the following 30 new species:  B. albipes, B. alytothrix, B. apterus, B. auranticeps, B. avignis, B. boliviensis, B. challabamba, B. costaricensis, B. cryptopygium, B. durango, B. emarginatus, B. friburguensis, B. guatemalensis, B. hispidus, B. hondurensis, B. inbio, B. longiphallus, B. masneri, B. machinator, B. oaxacensis, B. peruvianus, B. pollex, B. punctipennis, B. subemarginatus, B. subfoveolatus, B. suchixtepecensis, B. talamanca, B. wayqecha, B. zacapa, B. zamora. A key is provided for all known species.